If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.50(x + -3) = 2(x + -3) Reorder the terms: 0.50(-3 + x) = 2(x + -3) (-3 * 0.50 + x * 0.50) = 2(x + -3) (-1.5 + 0.50x) = 2(x + -3) Reorder the terms: -1.5 + 0.50x = 2(-3 + x) -1.5 + 0.50x = (-3 * 2 + x * 2) -1.5 + 0.50x = (-6 + 2x) Solving -1.5 + 0.50x = -6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1.5 + 0.50x + -2x = -6 + 2x + -2x Combine like terms: 0.50x + -2x = -1.5x -1.5 + -1.5x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 -1.5 + -1.5x = -6 + 0 -1.5 + -1.5x = -6 Add '1.5' to each side of the equation. -1.5 + 1.5 + -1.5x = -6 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + -1.5x = -6 + 1.5 -1.5x = -6 + 1.5 Combine like terms: -6 + 1.5 = -4.5 -1.5x = -4.5 Divide each side by '-1.5'. x = 3 Simplifying x = 3
| 6n+3n=108 | | f(-4)+f(3)= | | 30u^5v^3x^6+24u^8v^9= | | (4-2i)(3+i)= | | r*2+2r+12=0 | | 5.6+x=8.4 | | 3(19/-23)=20(-19/-23)-7 | | 3(19/-23)=20(-19/23)-7 | | 16x-3x=3(2-x) | | (3x^7)(-5x^3)= | | 12=-7y | | Xa+xb=3c | | x^4-x^3-24x^2+37x+60=0 | | 7(-8c+9a)= | | -3(4m+7)= | | 12=-11y+4y | | (-7v-6)-(2v-4)= | | 6(2+15x)= | | 2/7-1/14 | | 32b-4+-2b-1= | | 10+5r=10-r | | (2/x)-x=(-23/5) | | (7/8)/m=(1/7) | | =(2a+3b-4c) | | 4+5-2=33 | | -2y+6+9y= | | 2/3-1/x=5/3x | | 3(n-4)=-15 | | X*.38=112 | | 26x^2-130x+6=0 | | 4x^2-y^2=11 | | 14j+3k= |